Neutrophil/granulocyte transfusions collected from G-CSF + dexamethasone-stimulated donors. Issue 6 (November 2015) - Strauss, Ronald G.
Abstract : Purpose of review: The purpose of this review is to report a recently completed multicenter randomized controlled trial of neutrophil/granulocyte transfusions collected from G-CSF + dexamethasone donors to treat neutropenic infections in oncology and transplant patients, within the context of other historic and current clinical trials. The multicenter trial (RING Study) was funded by the NHLBI transfusion medicine/hemostasis clinical trials network. Recent findings: There was no significant benefit of therapeutic neutrophil/granulocyte transfusions versus antibiotics per intention to treat analysis, but 32% of patients received substandard neutrophil doses. Separate analysis suggested patients given a higher neutrophil doses had better outcomes. Summary: Efficacy of 'high-dose' therapeutic neutrophil/granulocyte transfusions remains unproven, but promising.